Current practices of Nepalese veterinarians for the clinical management of pain in animals - Shrestha, S.; Shah, M. K. (Journal of Agriculture and Forestry University, 2020)
The retrospective study was performed to know the trend of recent clinical practices for managing the post-surgical and non-surgical pain in animals. The study included government hospitals, private clinics, organizations working on animal birth control program of Chitwan, Kathmandu, Lalitpur, and Kaski districts of Nepal. Overall, 1,177 and 1,084 animals received analgesics in 2017 and 2018, respectively. Categorically, 81% of cases underwent for soft tissue surgeries, and analgesics were prescribed variably for 1–5 days. However, 5% and 1% were orthopedic and ophthalmic cases that were treated with analgesics for 1–8 days. Remaining, 13% cases that were grouped into miscellaneous type received analgesics for 1–7 days For analgesia, meloxicam was the most preferred non-steroidal anti-inflammatory drug (98%) followed by tramadol (9%), and lignocaine-HCl (8%). Tramadol (9%) and lignocaine-HCl (8%) were prescribed particularly in severely traumatized cases whereas ketorolac (5%) were used in orthopedic cases. Only 18% veterinary patients received preemptive analgesics. Most of the hospitals, clinics and organizations did not perform pain scoring. Proper pain assessment and their scoring are imperative for prescribing the right analgesic for the effective treatment of pain in animals.